Metodologije spremljanja cen gozdnih lesnih sortimentov v izbranih državah - Ščap, Špela (Acta silvae et ligni, 2022)
Monitoring the development of forest wood assortment prices is important for successful strategic planning, especially in the event of sudden changes in the wood market and in the implementation of trade policy. Revenue from forest wood assortment sales remains the most important criterion influencing the activity of forest owners or managers in intensifying forest management. The article presents data sources for prices of forest wood assortments in Slovenia and selected European countries and describes the main features of individual methods of collecting roundwood prices. After reviewing each of the methods used to collect prices for forest wood assortments, it was found that they differ from each other. In order to monitor the roundwood market, it is necessary to know and consider the criteria for defining the individual or group of forest wood assortments that are included in the statistics. However, caution should be exercised when comparing prices between individual sources, as the naming and classification of forest wood assortments varies from country to country and, in some places, from region to region. The article also compares prices for quality class B spruce logs among five different data sources for Slovenia, Austria, Germany, and the Czech Republic.
Keywords: cene; gozdni lesni sortimenti; okrogli les; razvrščanje; trg